Comparative analysis of criminal responsibility for encroachments on cultural values - Базелюк, В. В. (Theory and practice of jurisprudence, 2016)
Problem setting. The criminal codes of the most countries contain norms which foresee responsibility for encroachment on cultural values. Nowadays the necessity of comparative jurisprudence for Ukraine is obviously seen. Also the necessity of modernization of the judicial regulation of the social relations, the search of ways to avoid the mistakes of the states which successfully passed the corresponding period of development, increasing the amount of international contacts after proclamation of Ukrainian independence – everything is the evidence of the rationality of the activation in the field of comparative law. Paper objective. The purpose of this article is conducting the comparative analysis of criminal responsibility for encroachment on the cultural values after the Criminal code of Ukraine and legislation of such states as Russian Federation, Republic of Belarus, Republic of Kazakhstan, Republic of Turkmenistan, Republic of Uzbekistan, Kirghiz Republic, Republic of Poland, Denmark, France, Chinese People’s Republic. Unfortunately, the criminal codes of not all states contain the rules about responsibility for the crimes the subject of which cultural values are. For example, criminal codes of Holland, Switzerland and Sweden do not contain such norms. Conclusions of the research. Analysing the criminal legislation of some postSoviet and foreign countries in the sphere of the guard of cultural values we exposed both its advantages and disadvantages. In some states definite underestimation of no public unconcern of encroachments on sights of the history and culture (Holland, Switzerland, Sweden) is traced, in other – vice versa, its overvalue (CPR). From our point of view, the decision of questions of responsibility for encroachment on cultural values in the criminal codes of Russian Federation and France deserves on attention. Borrowing of definite experience of these countries will become a positive moment for the criminal guard of objects of archaeological and cultural inheritance in Ukraine. Key words: comparative analysis of criminal responsibility, cultural values, monuments of history and cultures, objects of archaeological and cultural inheritance, illegal archaeological excavations.